(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this research paper is provide a descriptive and an analytical study based on human relationships in Eliot’s The Cocktail Party. This play is about human relationships within the framework of marriage and outside it. Each person creates illusion about oneself and about others and therefore develops a personality that is not real. He covers his real face behind the mask. In order to achieve success in their relationships, human beings have to strip away the illusions and reveal their true self. They live in a modern society in the midst of many but do not have emotional relationship with anybody. They seek escape from their monotonous and boring life by arranging parties. They have no proper understanding of human relations. Due to failure of natural relations, they live in their private lives and become frustrated and self-deceiving persons. Eliot tries to find solution and creates awareness among characters of their potentialities and requirements.